Synthesis, Diagnosis and Microbiological Studies of Mn+2, Co+2, Ni+2, Cu+2 and Hg+2 Chelates of Two Schiff Bases Derived from O-Phathaldehyde - L.K. Abdul Karem (Journal of Global Pharma Technology, 2018)
A new Schiff base derivative ligands [H4L1] and [H2L2] have been produced by condensed o-phathaldehyde with ethylene diamine and [N1, N1’E, N1, N1’E)-N1, N1’-(1, 2-phenylenebis (methan-1-yl-1ylidene)) diethane-1, 2-diamine] with 2-benzoyl benzoic acid. Schiff base ligands have been separated and categorized by 1H, 13 C-NMR, (CHN) elemental analysis, UV-visible, mass spectroscopy and FTIR methods. Ten new coordination complexes were prepared and structurally diagnosed: [M(L1)Cl2] and [M2(L2)Cl2] where M(II) = Mn (II), Co(II), Ni(II),Cu(II) and Hg(II). The complexes have been typified by FTIR, UV-visble atomic absorption, molar conductance elemental analysis, and magnetic susceptibility. The details of the ligand (H4L1) compounds are getting an octahedral geometry while the complexes of ligand (H2L2) that are get square planar and tetrahedral geometries. Antimicrobial examinations show good results in the sharing complexes.Keywords: Schiff base, Antimicrobial, Diagnosis, O-phathaldehyde. Zz.